Exploring Elementary School Teachers' Perspectives on Culturally Responsive Teaching: Insights from Karimunjawa - Fatia Nur Azizah; Sarwanto Sarwanto; Roemintoyo Roemintoyo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Culturally Responsive Teaching (CRT) plays a vital role in promoting inclusive education. However, its implementation in geographically remote regions remains underexplored. This study investigates elementary school teachers’ perspectives on integrating CRT within the Independent Curriculum in the remote Karimunjawa District of Indonesia. A qualitative approach was employed involving ten public elementary school teachers. Data were collected through interviews, classroom observations, and document analysis. Triangulation of sources ensured the validity of findings. The data analysis involved reduction, presentation, and conclusion drawing. The findings indicate that while teachers generally recognize the importance of CRT and possess a basic understanding of its principles, significant barriers hinder effective implementation. These include limited access to professional development, lack of institutional support, and low confidence in applying CRT strategies. Teachers expressed a strong need for culturally relevant materials and methods to better engage students in reflecting on their cultural identities. The study highlights the unique challenges faced by educators in remote areas, particularly in adapting CRT to local contexts. It emphasizes the importance of culturally inclusive pedagogical practices and reveals gaps in training and resources. There is an urgent need for targeted CRT training, improved school support, and policy initiatives that prioritize culturally inclusive teaching in remote settings. These measures are essential to empower teachers and foster equitable learning environments across diverse educational landscapes.